Evaluating the performance of inflation targeting regime in three Asian economies - Sek Siok Kun (International Econometric Review (IER), 2012)
We conduct empirical analysis in evaluating the performance of inflation targeting (IT) in three emerging East-Asian economies that have implemented this regime. These three economies are Korea, Philippines and Thailand. The performance of inflation targeting regime is evaluated by comparing the economic achievement and structure changed between the pre- and post- IT periods. In particular, evaluation is focused on the inter-relationship between inflation and output growth / gap in these emerging economies between the pre- and post-IT periods. The inflation rate and the change in the macroeconomic variables are observed through country specific data. A bivariate GARCH (1,1) model is applied to study the inter-relationship between inflation and output gap. The results also enable us to detect if IT regime induces disinflation cost by causing lower growth or higher output gap. We compare the results of GARCH with the results of structural VAR for robustness checking. Both analyses provide consistent results. We observe lower inflation rate in the post-IT period. However, there is no significant correlation between inflation and output gap and we find no evidence that lower inflation causes lower growth or higher output gap. Both output gap and inflation are determined mainly by their own impulses. Besides, output gap is more persistent than inflation. We conclude that IT regime has improved the economies of these countries.
Keywords: C54; E58; E52; 330; inflation targeting; trade-off; persistency of shock; emerging markets